Should SVC flow be a routine measure when performing targeted neonatal echocardiography? A narrative review - Aimann Surak; Adrianne Bischoff (Elsevier, 2024)
Superior vena cava is commonly used in neonatal hemodynamics and is suggested to be the best available non-invasive marker for systemic circulation in preterm infants. Inter- and intra-observer variability remain to be an issue. Its association with neonatal outcomes is has not been established. This is a narrative review about this marker, its use, and its potential pitfalls. Objective: This is a narrative review about SVC flow in preterm infants, physiology, techniques of measurement and its potential association with outcomes. Sources: Literature revie mainly PubMED. Summary of the findings: SVC flow measurement has some limitations and pitfalls. Conclusions: SVC flow association with neonatal outcomes, still needs to be established in further research.